Update on the Role of Cellular Redox System in Health and Illness - Karayat, Manvi; Rahate, Kalpana; Singh, Shristi (Current Drug Discovery Technologies, 2025)
An imbalance between reactive oxygen species (ROS) and antioxidants in the circulatory system leads to oxidative stress, which has been linked to several pathological conditions, including cancer, aging, and neurological and cardiovascular diseases. Antioxidants play a crucial role in reducing oxidative damage by neutralizing harmful free radicals and preventing cellular injury. The processes generating cellular oxidative stress and the curative effects of antioxidants, the origins and effects of reactive oxygen species (ROS), the role that oxidative stress plays in the pathogenesis of disease, and the several kinds of antioxidants-including enzymatic and non-enzymatic antioxidants are thoroughly explored in this review. We also emphasized the medicinal uses of antioxidants, both natural and synthetic, in the prevention and treatment of disorders associated with oxidative stress. Furthermore, we discussed the challenges and potential paths ahead for antioxidant research, such as developing new antioxidant molecules with higher efficacy and improving antioxidant delivery systems. This study provides information regarding the complicated dynamics of oxidative stress and the potential benefits of antioxidants for preserving cellular homeostasis and advancing human health.
Keywords: enzymatic antioxidants